2015
DOI: 10.3390/ijms161024417
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro/In Vivo Toxicity Evaluation and Quantification of Iron Oxide Nanoparticles

Abstract: Increasing biomedical applications of iron oxide nanoparticles (IONPs) in academic and commercial settings have alarmed the scientific community about the safety and assessment of toxicity profiles of IONPs. The great amount of diversity found in the cytotoxic measurements of IONPs points toward the necessity of careful characterization and quantification of IONPs. The present document discusses the major developments related to in vitro and in vivo toxicity assessment of IONPs and its relationship with the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 179 publications
(197 reference statements)
7
122
2
Order By: Relevance
“…Iron oxide nanoparticles may come in different sizes, shapes, and crystalline forms, which may alter their toxicity. 53 It has been proposed that the ability of iron oxide nanoparticles to generate ROS is the most likely mechanism for their potential toxicity. 49 A study where iron oxide nanoparticles were orally administered at about 3 mg/kg body weight to rats over a 13-week period reported that they did not accumulate in tissues or produce toxicity.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…Iron oxide nanoparticles may come in different sizes, shapes, and crystalline forms, which may alter their toxicity. 53 It has been proposed that the ability of iron oxide nanoparticles to generate ROS is the most likely mechanism for their potential toxicity. 49 A study where iron oxide nanoparticles were orally administered at about 3 mg/kg body weight to rats over a 13-week period reported that they did not accumulate in tissues or produce toxicity.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…45,46 This behavior can be explained by the charge on the surface of iron oxide nanoparticles, which could play an important role in the intracellular uptake. 47 In this sense, there was no observable uptake of citrate-coated MNPs at concentrations of up to 0.1 mg/mL for murine macrophage cells (RAW 264.7) and Jurkat cell line (clone E6-1). At concentrations until 0.6 mg/mL, a relevant cellular uptake was observed, but the uptake of nanoparticles did not affect the viability and proliferation of the cells.…”
mentioning
confidence: 99%
“…It is in fact known that a significant number of newly synthesized nanocomposites successfully tested in in vitro models proved to be unsuitable when applied in vivo because of the systemic defense. 37 …”
Section: Ultrastructural Morphology For Nanotechnologymentioning
confidence: 99%